Analisis Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada CV. Bengawann Motor Samarinda - Umi Kulsum, Andi Merna Mutiara Adha 1 Eddy Soegiarto K (EKONOMIA, 2021)
The purpose of this study is : 1.) To find out the reliability affects the customer satisfaction at the CV. Bengawan Motor Samarinda. 2.) To find out responsiveness affects the customer satisfaction at CV. Bengawan Motor Samarinda. 3.) To find out the assurance effect on customer satisfaction at CV. Bengawan Motor Samarinda. 4.) To find out empathy affects customer satisfaction at the CV. Bengawan Motor Samarinda. 5.) To find out tangible affect customer satisfaction at CV.Bengawan Motor Samarinda. 6.) To find out the reliability, responsiveness, assurance, empathy, and tangible together affect customer satisfaction at the CV. Bengawan Motor Samarinda. The theory used in this research is service quality, price and customer satisfaction.This research was conducted at Samarinda Adi Service Workshop. Samples taken as many as 100 respondents with the Non Probability Sampling method with sampling techniques using Simple Random Sampling. Data collection by distributing questionnaires using a Likert scale to measure each indicator. The analytical tool in the study used multiple linear regression analysis using SPSS v23 statistical program tools.Analysis test equipment includes validity test, reliability test and multiple linear regression analysi. Then the interpolation of the results of data processing has been carried out by giving information explanation.The results showed that : 1.) Reliability variable has a significant effect on customer satisfaction at CV. Bengawan Motor Samarinda. 2.) Responsiveness variable has a significant effect on customer satisfaction at the CV. Bengawan Motor Samarinda. 3.) Assurance variable has no significant effect on customer satisfaction at the CV. Bengawan Motor Samarinda. 4.) Empathy variable has no significant effect on customer satisfaction at CV. Bengawan Motor Samarinda. 5.) Tangible variable has a significant effect on customer satisfaction at CV. Bengawan Motor Samarinda. 6.) The variables of reliability, responsiveness, assurance, empathy, and tangible together have a significant effect on customer satisfaction at the CV. Bengawan Motor Samarinda